Innovative design for optical porous silicon gas sensor - Acquaroli, Leandro Nicolás (2010)
A simple system for the detection of analytes in the atmosphere employing a freestanding nanostructured porous silicon optical microcavity was designed and built. The system is based on the measurement of optical transmittance changes as a function of the incidence angle of a monochromatic laser beam. Using a matrix formalism and effective medium theories we calculate the optimal conditions for the system so as to obtain the best sensitivity of the sensor. We tested the system over a detection area of the porous silicon microcavity of 100 micro m2 with isopropyl alcohol vapor diluted in a N2 stream. With the system proposed we were able to detect changes in the concentration of isopropyl alcohol as small as 1 ppm, which is equivalent to a change in the effective refractive index of about 3×10-6. The response time is very fast, lower than 0.5 s.